2008
DOI: 10.1016/j.neuropharm.2008.06.062
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxy-N-methamphetamine (ecstasy) promotes the survival of fetal dopamine neurons in culture

Abstract: Summary The current study examined whether modest concentrations of MDMA could increase the survival and/or neurite outgrowth of fetal midbrain dopamine (DA) neurons in vitro since increased DA neurite outgrowth has been previously observed in vivo from prenatal exposure. MDMA concentrations in fetal brain were quantified to determine relevant in vivo concentrations to employ in vitro. A dose-response study in vitro demonstrated that MDMA, at concentrations observed in vivo, resulted in increased, DA-specific,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…Noradrenergic fiber density was increased in the CA1 region of the HIPP, consistent with the former explanation, however fiber density was comparable to controls in the CA2 and CA3 region, suggesting that the relative innervation of these regions is comparable in both groups, but NET is upregulated in MDMA-treated subjects. We have previously reported findings consistent with the latter hypothesis in the DA system [27]. In this study, we demonstrated that MDMA increases Slc6a3 (DAT) gene expression in primary mesencephalic DA neurons in vitro , and that this was not a result of an increase in neurite density.…”
Section: Discussionsupporting
confidence: 89%
“…Noradrenergic fiber density was increased in the CA1 region of the HIPP, consistent with the former explanation, however fiber density was comparable to controls in the CA2 and CA3 region, suggesting that the relative innervation of these regions is comparable in both groups, but NET is upregulated in MDMA-treated subjects. We have previously reported findings consistent with the latter hypothesis in the DA system [27]. In this study, we demonstrated that MDMA increases Slc6a3 (DAT) gene expression in primary mesencephalic DA neurons in vitro , and that this was not a result of an increase in neurite density.…”
Section: Discussionsupporting
confidence: 89%
“…Ventral mesencephalon (VM) from Fisher 344 rats of embryonic day 14 (E14; crown‐rump length = 10.0–11.5 mm) containing developing A8, A9, and A10 dopamine cell groups was dissected from the ventral floor of the midbrain flexure extending posteriorly to the isthmus and laterally to the sulcus limitans (Lipton et al,2008). After collection, VM tissue was pooled in 4°C calcium‐magnesium‐free buffer, transferred to calcium‐magnesium‐free buffer containing 0.1% trypsin, warmed to 37°C for 10 minutes, rinsed in calcium‐magnesium‐free buffer again, and triturated in 0.004% DNase with Pasteur pipettes of 1.0‐mm and 0.5‐mm tip diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Paradoxically, localized direct administration of MDMA in rats by in vivo reverse microdialysis—at concentrations equivalent to those attained after high‐dose systemic administration—does not result in the typical indicators of serotonergic neurotoxicity, despite eliciting dramatically greater increases in extracellular monoamine levels 131 . Surprisingly, MDMA was demonstrated to exert neuroprotective effects in cultured rat fetal neurons, indicating that direct exposure to the chemical itself is not necessarily cytotoxic 132 . In addition, whereas systemically administered MDA and MDMA acutely increase the concentration of radical reactive oxygen species (ROS) and produce oxidative stress in the brain, direct intracerebroventricular administration is devoid of such effects 131,133 …”
Section: Possible Implications Of Dat Regulation To the Putative Toximentioning
confidence: 99%
“… Metabolic reaction pathway of MDA‐like compounds leading to the formation of neurotoxic prooxidant thioether species and the relative toxicity of metabolites. The parent compounds MDA and MDMA are not directly cytotoxic 131,132 . However, demethylenation of the 3,4‐methylenedioxy moiety by the hepatic CYP2D6 enzyme 135 results in the formation of 3,4‐dihydroxyamphetamines, which are readily oxidized to quinones 134 .…”
Section: Possible Implications Of Dat Regulation To the Putative Toximentioning
confidence: 99%